Social adaptation of sporting students: psycho-physiological health tests and analysis - Makunina O.А.; Bykov Е.V.; Kharina, I.F. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to test benefits of the sporting students’ social adaptation profiling psychophysiological health test system. Methods and structure of the study. We run the psychophysiological health testing educational experiment at the Environmental Stressors and Adaptation Research Laboratory of the Ural State University of Physical Culture’s Physiology Department in 2016 through 2020. We sampled, on a voluntary random basis, the first-, second- and third-year sporting Ural State University of Physical Culture students (n=254) and tested them for attention-deficit hyperactivity disorder (ADHD) symptoms by the Toulouse-Pieron test. Based on the test data, we further composed an Experimental group (n=25, 8.7%) of the ADHD-diagnosed students and Reference Group (n=25) of their ADHD-free peers. The groups were tested by the NS-PsychoTest set with prior verbal instructions. The nervous/ cardiovascular system functionality exposures to stressors were tested by the Loskutova Test. The regulatory system responses and stress tolerances were tested by the computerized Polyspectr-ANS Test system based on the heart rate variability profiles. The heart rate was measured for five minutes within some 300 cardiac cycles. The electrocardiograms were analyzed automatically with prior processing of artifacts. Based on the test data, we computed a stress index i.e. the heart rate control centralization ratio. The individual social adaptation progress was tested by the standard academic and competitive progress rating systems. Conclusion. The study data and analyses found the ADHD-diagnosed sporting students more exposed to stressors. A regression analysis showed the stress tolerance and nervous system functionality tests being beneficial for the sporting students’ social adaptation profiling purposes. The study findings demonstrate the need of the ADHD-diagnosed sporting students for an efficient social adaptation tracking service. Regular physical activity is recommended as beneficial for their emotional and social adaptation progress proved associated with the academic and competitive progress. The physical education faculties are recommended using a wide range of efficient individualized training methods, models and tools customizable for the psycho-physiological test data of the health group.